Hydrogenation of Carbon Dioxide to C2–C4 Hydrocarbons Catalyzed by Pd(PtBu3)2–FeCl2 with Ionic Liquid as Cocatalyst. Issue 19 (4th September 2019) - Wang, Huan; Zhao, Yanfei; Wu, Yunyan; Li, Ruipeng; Zhang, Hongye; Yu, Bo; Zhang, Fengtao; Xiang, Junfeng; Wang, Zhenpeng; Liu, Zhimin
Abstract: Direct hydrogenation of CO2 to C2+ hydrocarbons is very interesting, but achieving this transformation below 200 °C is challenging and seldom reported. Herein, a homogeneous catalytic system was developed composed of the ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([BMIm][PF6 ]), Pd(P t Bu3 )2, FeCl2, and the ligand 4, 5‐bis(diphenylphosphino)‐9, 9‐dimethylxanthene (Xantphos) for hydrogenation of CO2 under mild conditions, which resulted in C2 –C4 hydrocarbons in selectivities up to 98.3 C‐mol % at 180 °C. The combination of [BMIm][PF6 ]) with Xantphos endowed the Pd–Fe catalysts with the ability of activating CO2 and H2 simultaneously via [HPd(P t Bu3 )(BMIm‐COO)(BMIm)(PF6 )Fe] + species, thus catalyzing the formation of C2 –C4 hydrocarbons through CO2 hydrogenation. In addition, this catalytic system is stable and recyclable, which may have promising applications. Abstract : Short hydrocarbons : An ionic liquid (1‐butyl‐3‐methylimidazolium hexafluorophosphate; [BMIm][PF6 ])‐based Pd(P t Bu3 )2 –FeCl2 homogeneous catalytic system can realize CO2 hydrogenation to C2 –C4 hydrocarbons under mild conditions (e.g., 180 °C).